A Study on the Performance of IrOx Electrodes Prepared by Double-titanium Cyclic Voltametric Electrodeposition Mode - Wu Dandan; Wang Xi; Wu Xu (E3S Web of Conferences, 2022)
The electrodes were fabricated in double-titanium cyclic voltametric electrodeposition system, corresponding to the anode and cathode of the system. For further study the practicality of this mode, the performance of the resulting electrodes was investigated. Through a series of physical and electrochemical characterization, it is concluded that the IrOx electrode corresponding to the anode of the system has a flat and uniform deposit layer, and shows better electrolytic durability (its actual working life is more than 3072 h), while the cathode electrode has better performance in electrocatalytic activity.